Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Expanding the equation out gives

$(3^{2n}\times3)+(2^n\times2^2) \equiv 0\pmod{7}$

Is this correct? I'm a little hazy on my index laws.

Not sure if this is what I need to do? Am I on the right track?

share|improve this question
add comment

3 Answers

up vote 3 down vote accepted

Your initial calculation can lead to an answer.

Our expression is equal to $3(9^n)+4(2^n)$. Note that $9\equiv 2\pmod{7}$, and therefore $9^n\equiv 2^n \pmod{7}$. It follows that $$3(9^n)+4(2^n)\equiv 3(2^n)+4(2^n)=7(2^n)\equiv 0\pmod{7}.$$

share|improve this answer
No disrespect to Marvis' excellent and elaborate explanation but this short answer is exactly what I was looking for. Thanks! –  Arvin Nov 10 '12 at 3:01
add comment

$\rm \begin{eqnarray} {\bf Hint}\ \ \ a_{n\!+\!1}\!=2\,a_{n},\ b_{n\!+\!1}\!=9\,b_{n}\:\Rightarrow\: a_{n\!+\!1}\!+ b_{n\!+\!1} &\: =\: &\rm 2\ (\ a_{n}\!+b_{n}) + 7\,b_{n} \\ \rm hence\quad 7\mid a_{n\!+\!1}\!+ b_{n\!+\!1} &\rm \, if\, &\rm 7\mid a_{n}\!+b_{n}\end{eqnarray}$

share|improve this answer
add comment

Note that $$3^{2n+1} = 3^{2n} \cdot 3^1 = 3 \cdot 9^n$$ and $$2^{n+2} = 4 \cdot 2^n$$ Note that $9^{3k} \equiv 1 \pmod{7}$ and $2^{3k} \equiv 1 \pmod{7}$.

If $n \equiv 0 \pmod{3}$, then $$3 \cdot 9^n + 4 \cdot 2^n \equiv (3+4) \pmod{7} \equiv 0 \pmod{7}$$ If $n \equiv 1 \pmod{3}$, then $$3 \cdot 9^n + 4 \cdot 2^n \equiv (3 \cdot 9 + 4 \cdot 2) \pmod{7} \equiv 35 \pmod{7} \equiv 0 \pmod{7}$$ If $n \equiv 2 \pmod{3}$, then $$3 \cdot 9^n + 4 \cdot 2^n \equiv (3 \cdot 9^2 + 4 \cdot 2^2) \pmod{7} \equiv 259 \pmod{7} \equiv 0 \pmod{7}$$

EDIT What you have written can be generalized a bit. In general, $$(x^2 + x + 1) \vert \left((x+1)^{2n+1} + x^{n+2} \right)$$ The case you are interested in is when $x=2$.

The proof follows immediately from the factor theorem. Note that $\omega$ and $\omega^2$ are roots of $(x^2 + x + 1)$.

If we let $f(x) = (x+1)^{2n+1} + x^{n+2}$, then $$f(\omega) = (\omega+1)^{2n+1} + \omega^{n+2} = (-\omega^2)^{2n+1} + \omega^{n+2} = \omega^{4n} (-\omega^2) + \omega^{n+2} = \omega^{n+2} \left( 1 - \omega^{3n}\right) = 0$$ Similarly, $$f(\omega^2) = (\omega^2+1)^{2n+1} + \omega^{2(n+2)} = (-\omega)^{2n+1} + \omega^{2n+4} = -\omega^{2n+1} + \omega^{2n+1} \omega^3 = -\omega^{2n+1} + \omega^{2n+1} = 0$$

share|improve this answer
add comment

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.